2010
DOI: 10.5152/tjh.2010.43
|View full text |Cite
|
Sign up to set email alerts
|

Parvovirus-B19 and hematologic disorders

Abstract: Parvovirus-B19 (PV-B19) is a member of Parvoviridae, which is one of the smallest DNA viruses. PV-B19-associated diseases usually serve as a good representation of the balance of virus, host response and the immune system. The diseases manifested with PV-B19 are erythema infectiosum, which is common in children, hydrops fetalis, transient pure red cell aplasia in patients with chronic hemolytic anemia, arthralgia -mostly observed in women, and chronic pure red cell aplasia in immunocompromised individuals. Cyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
7
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 85 publications
1
7
0
1
Order By: Relevance
“…The present results provided evidence for the potential use of DBT on immune-mediated aplasia anemia mice (Yetgin and Elmas, 2010;Heckl et al, 2011). The findings indicated that three doses of DBT could not only withstand decreation of blood cells by immune-mediated, but also DBT administered at high dose group significantly increased the level of the WBC and HGB (p < 0.05).…”
Section: Discussionsupporting
confidence: 59%
“…The present results provided evidence for the potential use of DBT on immune-mediated aplasia anemia mice (Yetgin and Elmas, 2010;Heckl et al, 2011). The findings indicated that three doses of DBT could not only withstand decreation of blood cells by immune-mediated, but also DBT administered at high dose group significantly increased the level of the WBC and HGB (p < 0.05).…”
Section: Discussionsupporting
confidence: 59%
“…Maternal B19 IgM' nin ölçümü, akut B19 enfeksiyonu için oldukça duyarlı ve spesifik bir belirteç olabilir ancak, maternal kandaki B19 DNA'sının saptanması maternal B19 enfeksiyonunun tanımlanması için en iyi tanı hassasiyetine sahiptir ve viral DNA'nın saptanması, bağışıklığı baskılanmış hastalarda ve konjenital enfeksiyonda parvovirus B19 enfeksiyonunun teşhisinde önemlidir. Parvovirus B19 geçişini kontrol eden faktörler iyi anlaşılmamıştır ancak bununla birlikte, bağışıklık faktörlerinin önemli bir rol oynadığı düşünülmektedir[5][6][7][8].Enfeksiyon, gebeliğin 20. haftasında veya öncesinde ortaya çıktığı zaman fetal ölüm riski en fazla gözükmektedir. Parvovirusun neden olduğu fetal kayıp insidensi, enfeksiyonun endemik veya epidemik dönemde meydana gelip gelmediğine bağlı olarak da değişebilmektedir.…”
unclassified
“…Both in children and adults, B19 infections are generally considered a cause or trigger of various forms of autoimmune diseases such as rheumatoid arthritis (RA), idiopathic thrombocytopenic purpura (ITP), systemic lupus erythematosus (SLE) and other autoimmune hematologic diseases. [10][11][12][13][14][15][16] Although the association between HT and parvovirus B19 infection is demonstrated, the serological reflection of this association is not clear. The aim of this study was to test for antiparvovirus IgM and IgG antibodies in adult patients with HT.…”
mentioning
confidence: 99%